Особенности проектирования внутренних цепей питания микромощных БИС на основе элементов инжекционной логики - Belous, A. I.; Emel’yanov, V. A.; Syakersky, V. S.; Silin, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
Control of the ohmic resistance of “hidden layers” of the n+-type using a mathematical model based on an elementary cell of equivalent lumped conductance with partitioning along two coordinates makes it possible to significantly reduce the variation of numerical values of injector currents in I²L VLSI across the crystal surface and to decrease the overall crystal area by reducing the total metallization area of the power supply buses.